BUILDING DETERMINISTIC MODELS OF PRODUCT QUALITY DYNAMICS - Alexander G. Ivakhnenko; Vadim E. Puzanov (Advanced Engineering Research)
The deterministic models of the product quality dynamics based on the theoretical basics of the material systems kinetics are built. The dependence of the product quality change from the production complexity, resistance factors and requirements of consumers and other concerned parties, is received.